Hubungan Perilaku CERDIK terhadap Pengontrolan Tekanan Darah pada Lansia Hipertensi di Masa Pandemi COVID-19 - Seprina, Seprina; Herlina, Herlina; Bayhakki, Bayhakki (Holistic Nursing and Health Science, 2022)
Introduction: Most cases who suffer from hypertension are the elderly for that behavior is needed to control blood pressure, one of which is CERDIK behavior. CERDIK behavior consists of several lifestyles to improve and control health. So this study aims to find out how the relationship between CERDIK behavior on blood pressure control in the elderly during the COVID-19 pandemic.Methods: This study used a descriptive design with a cross sectional method. The sample in this study was 65 elderly people who were taken using purposive sampling and snowball sampling techniques. Data collection tools in this study were manual tensioner, stethoscope, and CERDIK Behavior questionnaire containing 19 questions that had been tested for validity (0.378-0.693) and reliability test (0.899). Inclusion criteria were respondents who were 60 years old, suffered from hypertension and were able to do physical activity. This research was conducted in Puskesmas Simpang Tiga, Pekanbaru City.Results: The results of this study indicate that majority elderly hypertensive people have cerdik behaviors good as many as 37 people (56.9%) and controlled arterial pressure of 35 people (53.8%). There is a significant relationship between cerdik behavior on blood pressure control with p values (0,005).Conclusion: As a result, it can be concluded that there is a significant relationship between cerdik behavior with control blood pressure in hypertension elderly during the Covid-19 period.